Makna Tradisi Pesta Lammang Bagi Masyarakat Lantang Kecamatan Polongbangkeng Selatan Kabupaten Takalar - Indriani Ayu Safitri; Mrs. Nurlela; St. Junaeda (Rayhan Intermedia, 2022)
This study aims to determine the series of implementation of the lammang party in Lantang Village, the meaning of the lammang party tradition for the community, and what values ​​are contained in the implementation of the lammang party. This study uses qualitative data with a descriptive approach. Data collection techniques through observation, documentation and interviews involving several informants. The results of this study indicate: 1). The process of implementing the lammang party tradition consists of anggalle bulo (taking bamboo), then ammone lammang (filling the lemang), attunu lammang (burning the lammang), angryang bungasa' (bringing the first lammang made or glutinous rice), and finally appasorong (pushing). go to the river. 2). The tradition of the lammang party is a tradition that has been carried out for a long time and is carried out every year after harvest. Apart from being a cultural heritage, the Lantang people interpret the tradition of the lammang party as a form of gratitude and gratitude to God for the harvest. Currently there are still people who do not carry out the ritual, even though the majority of people in Lantang Village still maintain and respect traditions that have been passed down from generation to generation. 3). The value contained in the implementation of the tradition of the lammang party is religious value. The value of art in the form of performing arts as entertainment and various kinds of competitions that can increase creativity and talent. Social values ​​are togetherness, mutual cooperation and strengthen friendship.